Methods of Changing or Correcting the Date of Birth - Reza Valavioun; Hamid farhami (پژوهشهای حقوقی)
Changing or correcting the date of birth is one of the important and basic issues in the field of civil law, which despite its importance and many plans in the administrative and judicial courts, has not been sufficiently considered, examined, and explained, therefore, its realization is necessary according to the case. Legal conditions are possible through three references and five methods. One method is to act through the commission to determine the age of the subject of the single article of the law on preserving the validity of registered documents, etc. Another method is to request the Dispute Resolution Board of the Civil Registry Office and the third method, which is actually the continuation of the process of obtaining the right through the previous method, is to protest the decision of this authority before the court and request its violation and accept the request from the court. The fourth way is to file a lawsuit to change or correct the date of birth before the court and the last method is to file a lawsuit to cancel the current registry document and issue a new registry document with the actual date of birth before the latter authority. In all cases, according to its type and the competent authority, the request is subject to the fulfillment of legal conditions and the presentation of justified evidence to the investigating authority.